Analisis Daya Dukung DAS Berdasarkan Kriteria Tata Air dan Daya Tampung Beban Pencemaran Sungai Gedek - Nesta Lilis Anggraeni; Yusrianti Yusrianti; Shinfi Wazna Auvaria; Amrullah Amrullah (Fakultas Teknik, 2021)
The increase in population every year and rapid economic development cause environmental problems related to the use of air resources. A need as what condition the water system to monitoring area stream the river in which to a variety problem environment. The purpose of this study was to determine the value of the load carrying capacity and assess the carrying capacity of the water management criteria. Based on the calculation of the pollution load capacity in class I, the parameters DO, COD, BOD, TSS and Ammonia exceed the load capacity of each of 3,325.07 mg/l, -9,872.32 mg/l, - 799,0063 mg/l, -271,705.21 mg/l, -664.06 mg/l. In class II that exceeds the load carrying capacity, the parameters DO, TSS, and Ammonia are 1,425.08 mg/l, -262.704.016 mg/l, -569.0619 mg/l, respectively. In class III, which exceeds the carrying capacity of the pollution load, the parameters DO, TSS, and Ammonia are 475.01 mg/l, -214.704.016 mg/l, -284.0558 mg/l, respectively. In class IV all parameters meet the pollution load capacity. The carrying capacity value based on the criteria of quality, quantity, and water continuity (water management) is 102.5 % included in the category.